2022
DOI: 10.19173/irrodl.v23i3.5894
|View full text |Cite
|
Sign up to set email alerts
|

Qualifying with Different Types of Quizzes in an Online EFL course: Influences on Perceived Learning and Academic Achievement

Abstract: This quasi-experimental study explored how different online exam types differentiate learners’ academic achievement and perceived learning. The participants comprised 95 undergraduate students enrolled in an English course at a Turkish university in three groups, each taking a different type of quiz: with multiple-choice, open-ended, and mixed type questions. The results indicated that the academic achievement of the students in multiple-choice and open-ended groups increased and that quiz results improved the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 33 publications
0
1
0
Order By: Relevance
“…Digital storytelling as a pedagogy combines technology, engagement, and entertainment and enables students to learn and develop deep thinking skills in an active exploration process [53], [54], [55]. Previous studies have shown that the barriers to digital storytelling in practice are technological issues and student autonomy [56], [57], [58], [59]. The research by Dogan and Robin [60] reported the competency of a teacher as a barrier in the way of digital storytelling implementation, and the study by Panchenko [61] established the lack of resources and resistance to innovation as a barrier to digital storytelling.…”
Section: Discussionmentioning
confidence: 99%
“…Digital storytelling as a pedagogy combines technology, engagement, and entertainment and enables students to learn and develop deep thinking skills in an active exploration process [53], [54], [55]. Previous studies have shown that the barriers to digital storytelling in practice are technological issues and student autonomy [56], [57], [58], [59]. The research by Dogan and Robin [60] reported the competency of a teacher as a barrier in the way of digital storytelling implementation, and the study by Panchenko [61] established the lack of resources and resistance to innovation as a barrier to digital storytelling.…”
Section: Discussionmentioning
confidence: 99%